Humant Development Indek and Maqoshid Syariah - sudarto, Aye; Imtihanah, Ani Nurul; Elmaza, Rina (Adzkiya : Jurnal Hukum dan Ekonomi Syariah, 2023)
In Islamic economic development, economic growth is not the final goal. Economic growth is an intermediate goal in achieving the final goal. Even so, economic growth does not automatically come with the advancement of human development. Nevertheless, the two will be interrelated and overshadow each other in the development of economic development and HDI. This research is a qualitative research. With qualitative research, researchers can identify objects, feel what a person experiences in everyday life. The stages of the research are carried out by selecting materials, focusing, simplifying, abstracting and organizing so that conclusions can be drawn from these materials. UNDP's concept of human development includes at least three indicators of human development: health, education and income. These three indicators are considered as elements that make up a successful life. These three indicators are the measurements used by UNDP in calculating the HDI of countries around the world, and based on the results of these calculations are used as a measure to classify countries as developed or underdeveloped. The five elements of I-HDI are based on Maqashid Syariah, so that Maqashid Syariah is appropriate to be used as a target for HDI and even becomes a broader concept of HDI.